THE STUDY OF THE PROPERTIES AND STRUCTURE OF CEMENT BINDING COMPOSITION ON ELECTROLYTE ACQUEOUS SOLUTIONS ACTIVATED BY MECHANOMAGNETIC METHOD - Ya.А. Sokolova,; M.V. Akulova,; B.R. Isakulov,; А.G. Sokolova,; B.B. Kul’sharov,; А.B. Isakulov, (Academic Scientific Journal of Chemistry, 2021)
In the present paper, the issues of studying the influence of complex activation of grouting fluid on the structure and properties of the hardened cement paste and concrete are considered. The problem is relevant for manufacturing of building materials. In the paper, there was used the method of applying in the concrete mix composition of the elementary chemical substances undergone special physical treatment by means of mechanomagnetic activation. For more profound study of the structure formation processes in the hardened cement paste, the method of differential thermo gravimetric analysis has been used. As the research results have shown, the concrete samples on the activated electrolyte solutions are characterized by improved strength. In addition, on the base of differential thermo gravimetric analysis, it was proven that in the studied samples of the hardened cement paste on the electrolyte solutions activated by the method of mechanomagnetic treatment, the less calcium hydroxide and the more hydrated calcium silicate with amorphous and fine crystalline is formed. The obtained results for cement composites could be applied when manufacturing effective binder for concretes and mortars in the production of building materials and structures